Efektivitas Layanan Bimbingan dan Konseling dalam Pemantapan Pemilihan Karir Siswa SMA : A Systematic Literature Review (SLR) (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Determining a career choice is not easy because there are many things to consider. Strengthening career selection is the most important part and must be owned by students to support future career success. This study aims to determine group services and counseling with several practical techniques for strengthening student careers. The research method used is a systematic Literatur Review ( SLR) by collecting Sinta-indexed national journals and Scopus-indexed international journals from 2013-2023. Data analysis uses a qualitative meta-synthesis method approach, which is a method that seeks to identify, assess, and interpret the overall results of the research following the research question or phenomenon as a study. The results of the literature found various group counseling techniques used to strengthen job selection, such as Cognitive Behavior Therapy (CBT); Solution- Focused Brief Counseling( SFBC); Traits And Factors; Problem-Solving; wants, doing, evaluating, planning (WDEP), Dispute Irrational Belief, Ability Potential Response dan Live Modeling, Mind Mapping,  Group Discussion, and John L. Holland's Career Interest Test. The conclusion is that group counseling and guidance with various proven techniques effectively increase students' deepening career determination in high school students.